Baseline demographics and disease characteristics of patients with episodic or chronic cluster headache: data from two phase 3 randomized clinical trials in Europe and North America - Jensen, Rigmor Hoejland; Tassorelli, Cristina; Myers Oakes, Tina M.; Bardos, Jennifer N.; Zhou, Chunmei; Dong, Yan; Aurora, Sheena K.; Martinez, James M. (Frontiers in Neurology, 2023)
Objective Two phase 3 galcanezumab trials were conducted in Europe and North America to analyze the reduction of weekly cluster headache (CH) attack frequency in populations with episodic and chronic CH. The current study aims to illustrate prospectively recorded baseline clinical data from these trials and to identify possible predictors of response. Methods Patients (aged 18–65 years) met The International Classification of Headache Disorders 3rd edition-beta criteria for CH. Attacks were evaluated using an electronic headache diary for 7-day (episodic) or 14-day (chronic) eligibility assessments before patients were randomized 1:1 to monthly subcutaneous galcanezumab 300 mg or placebo. Results Data were collected from 106 patients with episodic and 237 with chronic CH. Overall, the mean age [standard deviation] was 45.4 [11.0] years; patients were predominantly White (84.5%), male (75.8%), and European (77.6%). Patients with episodic CH reported 17.5 [10.0] attacks/week; patients with chronic CH reported 18.8 [10.2] attacks/week. The average pain severity score (range 0–4) was 2.5 [0.7] for episodic CH and 2.7 [0.7] for chronic CH. Higher attack frequency was a possible predictor of response to galcanezumab; potential negative predictors of response were greater attack severity and duration. Conclusion This large dataset of patients with CH provides reliable systematically and prospectively collected information on disease characteristics. The analysis in episodic CH underscores potential predictors of response worth considering for future CH trial design. Clinical Trial Registration ClinicalTrials.gov, identifiers: NCT02397473 and NCT02438826.